Patterns, risk factors and characteristics of reported and perceived foot-and-mouth disease (FMD) in Uganda - Ayebazibwe, Chrisostom; Tjørnehøj, Kirsten; Mwiine, Frank N.; Muwanika, Vincent B.; Okurut, Anna Rose Ademun; Siegismund, Hans R.; Alexandersen, Soren (Tropical Animal Health and Production, 2010)
Patterns of outbreaks of foot-and-mouth disease (FMD) in Uganda were elucidated from spatial and temporal retrospective data retrieved from monthly reports from District Veterinary Officers (DVOs) to the central administration for the years spanning 2001–2008. An assessment of perceived FMD occurrence, risk factors and the associated characteristics was made based on semi-structured questionnaires administered to the DVOs. During this period, a total of 311 FMD outbreaks were reported in 56 (70%) out of Uganda’s 80 districts. The number of reported FMD outbreaks changed over time and by geographical regions. Occurrence of FMD was significantly associated with the dry season months (p = 0.0346), the time when animals movements are more frequent. The average number of FMD outbreaks was higher for some sub-counties adjacent to national parks than for other sub-counties, whilst proximity to international border only seemed to play a role at the southern border. DVOs believed that the major risk factor for FMD outbreaks was animal movements (odds ratio OR 50.8, confidence interval CI 17.8–144.6) and that most outbreaks were caused by introduction of sick animals.
Keywords: Foot-and-mouth disease outbreaks . Occurrence . Sub-counties . Uganda